Previous Extrapulmonary Malignancies Impact Outcomes in Patients With Surgically Resected Lung Cancer - Lee, Hsin-Ying; Hsieh, Min-Shu; Liao, Hsien-Chi; Chen, Pei-Hsing; Chiang, Xu-Heng; Tsou, Kuan-Chuan; Tsai, Tung-Ming; Chuang, Jen-Hao; Lin, Mong-Wei; Hsu, Hsao-Hsun; Chen, Jin-Shing (Frontiers in Surgery, 2021)
Background: As the overall survival of patients with cancer continues to improve, the incidence of second primary malignancies seems to be increasing. Previous studies have shown controversial results regarding the survival of patients with primary lung cancer with previous extrapulmonary malignancies. This study aimed to determine the clinical picture and outcomes of this particular subgroup of patients. Materials and Methods: We included 2,408 patients who underwent pulmonary resection for primary lung cancer at our institute between January 1, 2011 and December 30, 2017 in this retrospective study. Medical records were extracted and clinicopathological parameters and postoperative prognoses were compared between patients with lung cancer with and without previous extrapulmonary malignancies. Results: There were 200 (8.3%) patients with previous extrapulmonary malignancies. Breast cancer (30.5%), gastrointestinal cancer (17%), and thyroid cancer (9%) were the most common previous extrapulmonary malignancies. Age, sex, a family history of lung cancer, and preoperative carcinoembryonic antigen levels were significantly different between the two groups. Patients with previous breast or thyroid cancer had significantly better overall survival than those without previous malignancies. Conversely, patients with other previous extrapulmonary malignancies had significantly poorer overall survival (p < 0.001). The interval between the two cancer diagnoses did not significantly correlate with clinical outcome. Conclusion: Although overall survival was lower in patients with previous extrapulmonary malignancies, previous breast or thyroid cancer did not increase mortality. Our findings may help surgeons to predict prognosis in this subgroup of patients with primary lung cancer.